Bacteriology and antibiotic sensitivity patterns in ventilator-associated pneumonia - Ranjit, Srijana; Katuwal, Nishan; Ranjit, Sangina (Journal of Chitwan Medical College, 2021)
Background: Ventilator-Associated Pneumonia is the most common cause of hospital-acquired infections among patients admitted in Intensive Care Unit with mechanical ventilation. Identification of bacteria and their susceptibility to commonly used antibiotics is very essential for the treatment of the patients. The aim of this study was to determine the bacteriological profile and antibiotic sensitivity patterns in the Endotracheal Aspirate cultures that were sent in Microbiology laboratory. Methods: A hospital-based 3-year retrospective analysis on culture of Endotracheal Aspirate was done. Data from Intensive Care Unit was collected from January 2018 to January 2021, and the laboratory reports were used to determine Ventilator-Associated Pneumonia, pathogen profile and antimicrobial sensitivity patterns. Data entry and analysis was done using Statistical Package for Social Sciences version 16. Results: Out of 147 ventilated patients in Intensive Care Unit, 115 samples were sent to microbiology laboratory with suspected Ventilator-Associated Pneumonia among which 95 (82.60 %) were positive cultures. The most common etiological agent causing Ventilator-Associated Pneumonia was found to be Klebsiella pneumoniae with 24 isolates (25.26%) and multidrug resistance was also mainly found with Klebsiella pneumoniae in 17 samples (70.83%). All of the gram-negative isolates were sensitive to colistin and resistant to ampicillin. All gram-positive isolates were sensitive of linezolid and vancomycin and most were resistant to penicillin. Conclusions: Klebsiella pneumoniae is one of the most common organisms that is associated with nosocomial infection like Ventilator-Associated Pneumonia. The emergence of multidrug resistance is still a great threat and hindrance for the treatment of Ventilator-Associated Pneumonia.